2018
DOI: 10.1111/ctr.13192
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of free wall radial motion in global right ventricular function of heart transplant recipients

Abstract: Assessment of right ventricular (RV) function using conventional echocardiography might be inadequate as the radial motion of the RV free wall is often neglected. Our aim was to quantify the longitudinal and the radial components of RV function using three-dimensional (3D) echocardiography in heart transplant (HTX) recipients. Fifty-one HTX patients in stable cardiovascular condition without history of relevant rejection episode or chronic allograft vasculopathy and 30 healthy volunteers were enrolled. RV end-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 49 publications
7
29
0
1
Order By: Relevance
“…This surgery pattern resulted in a significantly lower TAPSE value related to the global and segmental RV function decreased with myocardial longitudinal strain mechanics detection. In addition, we found similar results in the studies by Moñivas et al 8 and Lakatos et al 16–19 This evaluation detected impaired RV and stable LV functions from our studies, and monitored recovered or improved strain values during the 1‐, 5‐year than that in 1‐, 3‐month follow‐ups. Even though still reduced strain than controls we assessed, it was different than what Moñivas et al 8 revealed.…”
Section: Discussionsupporting
confidence: 92%
“…This surgery pattern resulted in a significantly lower TAPSE value related to the global and segmental RV function decreased with myocardial longitudinal strain mechanics detection. In addition, we found similar results in the studies by Moñivas et al 8 and Lakatos et al 16–19 This evaluation detected impaired RV and stable LV functions from our studies, and monitored recovered or improved strain values during the 1‐, 5‐year than that in 1‐, 3‐month follow‐ups. Even though still reduced strain than controls we assessed, it was different than what Moñivas et al 8 revealed.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, conventional M-mode and 2D indices may be inadequate for the post-operative assessment of RV function. 20 Our results clearly demonstrated that the radial motion could effectively compensate for the post-operative decline of longitudinal motion to maintain RVEF. Interestingly, we have found that 6 months after the successful operation, the native contraction pattern is restored in MVR patients as RV longitudinal and radial contributions (LEFi, REFi) are comparable with healthy controls'.…”
Section: Adaptation To Chronic Primary Mitral Valve Regurgitationsupporting
confidence: 58%
“…Under physiological conditions, the longitudinal shortening was suggested to account for the majority of RV pump function [ 5 ]; however, the majority of recent studies suggest a similar importance of longitudinal and radial motions (Fig. 2 ) [ 6 , 7 ]. Larger studies are needed to characterize potential age-related and gender-related alterations.…”
Section: Functional Pattern Of Rv Myocardial Mechanicsmentioning
confidence: 99%